Deletion of Ribosomal S6 Kinases Does Not Attenuate Pathological, Physiological, or Insulin-Like Growth Factor 1 Receptor-Phosphoinositide 3-Kinase-Induced Cardiac Hypertrophy - McMullen, Julie R. (American Society for Microbiology, 2004)
Ribosomal S6 kinases (S6Ks) have been depicted as critical effectors downstream of growth factor pathways, which play an important role in the regulation of protein synthesis by phosphorylating the ribosomal protein, S6. The goal of this study was to determine whether S6Ks regulate heart size, are critical for the induction of cardiac hypertrophy in response to a pathological or physiological stimulus, and whether S6Ks are critical downstream effectors of the insulin-like growth factor 1 (IGF1)-phosphoinositide 3-kinase (PI3K) pathway. For this purpose, we generated and characterized cardiac-specific S6K1 and S6K2 transgenic mice and subjected S6K1(−/−), S6K2(−/−), and S6K1(−/−) S6K2(−/−) mice to a pathological stress (aortic banding) or a physiological stress (exercise training). To determine the genetic relationship between S6Ks and the IGF1-PI3K pathway, S6K transgenic and knockout mice were crossed with cardiac-specific transgenic mice overexpressing the IGF1 receptor (IGF1R) or PI3K mutants. Here we show that overexpression of S6K1 induced a modest degree of hypertrophy, whereas overexpression of S6K2 resulted in no obvious cardiac phenotype. Unexpectedly, deletion of S6K1 and S6K2 had no impact on the development of pathological, physiological, or IGF1R-PI3K-induced cardiac hypertrophy. These studies suggest that S6Ks alone are not essential for the development of cardiac hypertrophy.